Mathematical Model of the Controlled Object when Regulating the Working Volume of the Manipulator Pump - F. Bairamov, Bulat; A. Fardeev, Artur; R. Fardeev, Albert (International Journal of Engineering and Technology, 2018)
This paper describes the constructed mathematical model of the controlled object of the automated system for controlling the displacement volume of the manipulator pump. The change in pump displacement volume is performed in order to save energy by minimizing the fluid drain through the overflow valve. The use of the considered manipulator is intended in the process of automated supply of blanks to the working area of a press used in forging and hot stamping processes. The reactive forces acting on the moving parts of the mobility modules from the fixed parts of the manipulator are determined. Conversion of the useful power of the pump into the useful power of hydraulic motors is performed. This takes into account the losses using efficiency. An equation describing the mathematical model of the controlled object is obtained. This equation is represented in relative variables. The derivation of this equation and the determination of the reactive forces are made on the basis of the assumption that all transport degrees of freedom are translational. This limitation is caused by the peculiarities of the working area of the press used in technological processes of forging and hot forming of blanks. The working zone is a deep horizontal tunnel, the movement of the working object in which is possible only with translational degrees of freedom.Â Â